Design dialyzátoru - Zdvihalová, Markéta (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2014)
Hlavním cílem této diplomové práce je návrh dialyzátoru. Práce by měla ukázat vlastní tvůrčí myšlení a kreativitu autora práce. Ačkoliv musí návrh splňovat obecné technické, konstrukční a ergonomické předpoklady, přesto by měl být design tvořen s ohledem na moderní technologie. Cílem je tedy také posunout design z čistě technické oblasti do oblasti estetiky a praktičnosti.

The main aim of this master’s thesis is design of dialysis machine. This thesis should demonstrate author’s creative thinking and creativity. This design has to satisfy the general technical, ergonomic and design assumptions, but it should be designed with modern technology. The aim is also to show the ability to move an object from the field of functionality to the field od aesthetic, ergonimics and practicality.
Design of Dialysis Machine
Keywords: Dialyzační přístroj; dialyzátor; dialýza; organické; design; Dialysis machine; dialyser; dialysis; organic; design